Endogenous Hypercortisolism in recurrent Central Serous Chorioretinopathy - Mukherji, Sushmita; Karmakar, Soumen; Dasgupta, Sibaji (Asian Journal of Medical Sciences, 2021)
Background: Central Serous Chorioretinopathy (CSCR) is an important cause of nonsurgical retinopathy leading to moderate to severe visual loss. Almost 50% cases undergo recurrence, and one of the recognizable risk factors is endogenous hypercortisolism. Aims and Objective: Our study intended to its presence in recurrent CSCR patients compared to non-chorioretinal disorder. Materials and Methods: Eighteen-month cross-sectional comparative study done on recurrent CSCR patients and matched refractive error patients comprised the comparison group. Use of exogenous steroids and diagnosed conditions of hypercortisolism were excluded. Sample size for both the groups was 34 in each. After taking history and performing ocular examination, blood samples for serum cortisol estimation collected in the morning and in the evening in patients of both the groups. Results analyzed using standard statistical methods. Results: All patients of recurrent CSCR were males. The mean serum levels of cortisol were higher than laboratory reference range during both times of the day in recurrent CSCR patients, and these levels were significantly higher than those in the comparison groups. Conclusion: Recurrent CSCR patients have higher level of endogenous cortisol compared to the non-chorioretinal patients, and its early recognition and management would certainly benefit the patients.